Is there an employee-based gender gap in informal financial markets? International evidence - An, Jiafu (Journal of Corporate Finance, 2020)
We study the impact of female production workers on firms' access to trade credits across the world. Using two sources of plausibly exogenous variations in gender bias and a difference-in-differences framework, we document that firms with more female production workers have less access to trade credits in countries with stronger gender beliefs that favor males. This relationship is largely driven by firms in industries with unexpected credit shortages and industries dominated by males. Since female firms rely more on informal finance, this study is relevant for policies that direct female firms towards formal credit markets in highly gender-biased places.